Chromatic pupillometry isolation and evaluation of intrinsically photosensitive retinal ganglion cell-driven pupillary light response in patients with retinitis pigmentosa - Zhao, He; Wang, Hao; Zhang, Minfang; Weng, Chuanhuang; Liu, Yong; Yin, Zhengqin (Frontiers in Human Neuroscience, 2023)
Purpose. The pupil light response (PLR) is driven by rods, cones, and intrinsically photosensitive retinal ganglion cells (ipRGCs). We aimed to isolate ipRGC-driven pupil responses using chromatic pupillometry and to determine the effect of advanced retinitis pigmentosa (RP) on ipRGC function. Methods. 100 eyes from 67 patients with advanced RP and 18 healthy controls (HCs) were included. Patients were divided into groups according to severity of visual impairment: no light perception (NLP, 9 eyes), light perception (LP, 19 eyes), faint form perception (FFP, 34 eyes), or form perception (FP, 38 eyes). Pupil responses to rod-weighted (487 nm, -1 log cd/m 2 , 1 s), cone-weighted (630 nm, 2 log cd/m 2 , 1 s), and ipRGC-weighted (487 nm, 2 log cd/m 2 , 1 s) stimuli were recorded. ipRGC function was evaluated by the postillumination pupil response (PIPR) and three metrics of pupil kinetics: maximal contraction velocity (MCV), contraction duration, and maximum dilation velocity (MDV). Results. We found a slow, sustained PLR response to the ipRGC-weighted stimulus in most patients with NLP (8/9), but these patients had no detectable rod-or cone-driven PLR. The ipRGC-driven PLR had an MCV of 0.269 ± 0.150%/s and contraction duration of 2.562 ± 0.902 s, both of which were significantly lower than those of the rod and cone responses. The PIPRs of the RP groups did not decrease compared with those of the HCs group and were even enhanced in the LP group. At advanced stages, ipRGC responses gradually became the main component of the PLR. Conclusion. Chromatic pupillometry successfully isolated an ipRGC-driven PLR in patients with advanced RP. This PLR 批注 [赵1]: Reviewer 3: Comments 2 remained stable and gradually became the main driver of pupil contraction in more advanced cases of RP. Here, we present baseline data on ipRGC function; we expect these findings to contribute to evaluating and screening candidates for novel therapies.